2022
DOI: 10.7759/cureus.25867
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities in Survival Among Non-Hodgkin Lymphoma Patients: An Analysis of the SEER Database (2007-2015)

Abstract: Introduction Although disparities in cancer survival exist across different races/ethnicity, the underlying factors are not fully understood. Aim To identify the interaction between race/ethnicity and insurance type and how this influences survival among non-Hodgkins lymphoma (NHL) patients. Methods We utilized the SEER (Surveillance, Epidemiology, and End Results) Registry to identify patients with a primary diagnosis of NHL from 2007 to 2015. Our primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In a cohort of 1,605 patients with Hodgkin lymphoma treated in the Children’s Oncology Group trials between 2002 and 2012,69 non-White patients (pooled Black and Hispanic) had a 1.88 -fold increased risk of mortality in multivariable analyses [ 23 ]. Abodunrin et al found significant differences in the disease distribution and relative survival of NHL patients among the different racial groups in the United States [ 24 ]. Li et al found a significantly higher five-year relative survival in Whites with stages I-IV DLBCL compared to Blacks, Asians, and Pacific Islanders, while Blacks have the worst five-year relative survival among patients with stage I-III, and Asians/Pacific Islanders have the worst survival in stage IV [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a cohort of 1,605 patients with Hodgkin lymphoma treated in the Children’s Oncology Group trials between 2002 and 2012,69 non-White patients (pooled Black and Hispanic) had a 1.88 -fold increased risk of mortality in multivariable analyses [ 23 ]. Abodunrin et al found significant differences in the disease distribution and relative survival of NHL patients among the different racial groups in the United States [ 24 ]. Li et al found a significantly higher five-year relative survival in Whites with stages I-IV DLBCL compared to Blacks, Asians, and Pacific Islanders, while Blacks have the worst five-year relative survival among patients with stage I-III, and Asians/Pacific Islanders have the worst survival in stage IV [ 25 ].…”
Section: Discussionmentioning
confidence: 99%